2020
DOI: 10.23917/jiti.v19i2.10718
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting The Implementation of Green Procurement: Empirical Evidence from Indonesian Educational Institution

Abstract: This paper reported the factors affecting the adoption of green procurement in Indonesian educational institutions.  A quantitative method is used to understand the effects between variables on green procurement implementation. Data from respondents working on the divisions of procurement from higher degree institutions in the province of East Java Indonesia are collected in this study. The results were indicated that there are no significant effects on middle management staff, awareness, and corporate respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
4
3
0
Order By: Relevance
“…The majority of respondents (mean = 3.6) concurred that the supplied products were TBS and ISO 9001 certified. This conclusion is in agreement with that of Masudin et al (2020) who found that the supplied goods within the organization were certified by the organization.…”
Section: Effect Of Supplier Awareness On Sustainable Procurementsupporting
confidence: 92%
See 4 more Smart Citations
“…The majority of respondents (mean = 3.6) concurred that the supplied products were TBS and ISO 9001 certified. This conclusion is in agreement with that of Masudin et al (2020) who found that the supplied goods within the organization were certified by the organization.…”
Section: Effect Of Supplier Awareness On Sustainable Procurementsupporting
confidence: 92%
“…The respondents also concurred that the provided goods are eco-design items (mean 3.3). This result agrees with those of Masudin et al (2020), who also found that the supplier provided the eco-design goods. Lastly, respondents were questioned regarding the certification of the supplied goods or products (ISO 900 & TBS).…”
Section: Effect Of Supplier Awareness On Sustainable Procurementsupporting
confidence: 92%
See 3 more Smart Citations